WITHDRAWN: An anatomic aberration and a surgical challenge: Mediastinal parathyroid adenoma anterior the pericardium. A case report. (2019) - Patrinos, Antonios; Zarokosta, Maria; Piperos, Theodoros; Chrysikos, Dimosthenis; Kakaviatos, Dimosthenis; Theodoropoulos, Panagiotis; Kalles, Vasileios; Tsiaoussis, John; Noussios, George; Mariolis-Sapsako, Theodoros
Abstract : The Publisher regrets that this article is an accidental duplication of an article that has already been published in "International Journal of Surgery Case Reports, 57C (2019) 106–109", https://doi.org/10.1016/j.ijscr.2019.03.014 . The duplicate article has therefore been withdrawn. The full Elsevier Policy on Article Withdrawal can be found at https://www.elsevier.com/about/our-business/policies/article-withdrawal